Implementation Of Talent Management System Through Management Trainee as Future Leader and Successor Planning (Best Practice) - hendriyana, Hendriyana; Sirait, Tongam (Enrichment: Journal of Multidisciplinary Research and Development, 2024)
This study aims to examine the implementation of a talent management system through a Management Trainee program based on the Indonesian National Work Competency Standards (SKKNI) in the Bottled Drinking Water (AMDK) industry. Management trainee is one of the effective methods to develop future leaders and superior talents in the organization. The SKKNI approach in this program ensures that the employees developed have competencies that are in line with national standards. The management trainee program can significantly improve employees' skills and knowledge, as well as make a positive contribution to employee productivity and retention in the company. The managerial implication of this research is the importance of investing in the development of a structured and measurable management trainee program to achieve the organization's strategic goals. The sample in this study were 12 talents who participated in the management trainee program for 12 months. The results showed that the company has succeeded in aligning talent strategy with business strategy, developing future leaders and conducting comprehensive evaluations in carrying out talent management